The Development and Validation of The Indonesian Insulin Adherence Influence Factor Questionnaire (IIAIFQ) - Yuniarti Suryatinah; Umi Athiyah; Adliah Binti Mohd Ali; Elida Zairina (Universitas Airlangga, 2023)
Background: Type 2 diabetes mellitus (DMT2) is a metabolic disease due to abnormalities in insulin secretion. Insulin is one of DMT2 therapy. Objective: This study aimed to validate a modified the insulin adherence influence factor questionnaire based on the health belief model (HBM) among Indonesian patients with DMT2. Methods: The Indonesian insulin adherence influence factor questionnaire (IIAIFQ) was developed based on modified some literature reviews and internal expert discussions. The study included 30 participants aged â‰¥ 17 y.o years old who had been taking insulin in the previous two months. The questionnaire consists of seven dimensions to measure HBM : perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, cues to action and insulin adherence. Results: The construct validity test showed that of the 34 question items in the questionnaire, 10 items were invalid, 24 others were demonstrated valid based on the Pearson Correlation (>r table 0.361; p<0.05; loading factor > 0.5). Furthermore, 24 valid items were tested for reliability at a significance level of 0.05, and the results showed that each size had a Cronbach's Alpa > 0.6 with an overall score was 0.858, indicating that all domains in the questionnaire were reliable. Conclusion: IIAIFQ based The HBM theory is a valid and reliable instrument for assessing insulin adherence in diabetes mellitus patients.